Pediatric Orthopedic Trauma in Pakistan: Injury Mechanisms, Fracture Patterns, and Surgical Outcomes - Muhammad Sabir Memon, Humera Ismail, Ghazanfar Ali Shah, Muhammad Yousuf Memon, Aashish Kumar Sachdev, Kundan Shah Ghulam Rasool, Nooruddin Rahujo, Tanveer Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pediatric orthopedic trauma represents a major public health concern in low- and middle-income countries, where road traffic injuries and falls contribute disproportionately to childhood morbidity and disability. Understanding local injury patterns and management practices is essential for improving trauma care delivery in Pakistan. Methods: This retrospective descriptive study was conducted at the Orthopedic Department of the Shaheed Mohtarma Benazir Bhutto Institute of Trauma (SMBBIT), Karachi, from January 2017 to December 2022. A total of 947 children aged 1-18 years presenting with orthopedic trauma were included. Data extracted from the trauma registry and medical files included demographics, mechanism of injury, fracture patterns, management strategies, and clinical outcomes. Statistical analysis was performed using SPSS version 27, with significance set at p ≤ 0.05. Results: Of the 947 children included, the mean age was 14.86 ± 2.12 years, and 88.1% were male. Bike-related accidents (48.5%) and falls (27.6%) were the predominant mechanisms of injury, followed by motor-vehicle collisions (8.8%) and pedestrian injuries (8.2%). Blunt trauma accounted for 96% of all cases. Femur fractures were most common (52.3%), followed by humerus fractures (12.5%). A total of 881 surgical procedures were performed, primarily external fixation (29.8%), internal fixation (24.1%), and wound debridement (16.4%). Most children (71.2%) were discharged, while mortality occurred in 0.8% and LAMA in 0.2% of cases. Conclusion: Pediatric orthopedic trauma at this tertiary center was predominantly caused by high-energy mechanisms, particularly motorcycle accidents and falls, leading to a substantial need for surgical intervention. The findings underscore the need for strengthened injury-prevention strategies, improved road-safety enforcement, and enhanced pediatric trauma care systems in Pakistan. Keywords: Pediatric Trauma, Orthopedic Injuries, Fracture Fixation, Wounds and Injuries Epidemiology, Road Traffic Accidents.